PROGRESSIVE IOT PLATFORM BASED ON EDGE COMPUTING TECHNOLOGY - NIKOLSKIY, SERHIY; KLYMENKO, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article introduces a cutting-edge IoT platform that capitalizes on edge computing technology, revolutionizing data processing and analysis in the Internet of Things (IoT) landscape. By relocating data collection, processing, and analysis functions to the local level of the IoT network, the platform effectively mitigates delays and reduces excessive data transmission costs associated with the global network. The core architectural concept revolves around an autonomous multifunctional processing center, responsible for executing crucial tasks, including data collection, real-time processing, and comprehensive analysis from IoT devices. Additionally, it facilitates system visualization, monitoring based on diverse indicators, and offers a wide array of user services. The platform's functional model caters to various domains, fostering innovation and efficiency. A prototype IoT platform has been developed to conduct experimental analysis, assessing the hardware and technical capabilities of the proposed tools, thus paving the way for further advancements and refinements. The architecture comprises three primary components: IoT devices, the edge processing center, and a user-friendly interface. IoT devices equipped with sensors collect data, transmitted to the edge processing center for real-time analysis, considerably reducing global network data transmission requirements. As a result, the platform significantly enhances cost-effectiveness and responsiveness. In conclusion, this article showcases a transformative IoT platform, empowered by edge computing, streamlining data processing, and analysis. The multifunctional processing center serves as the linchpin, surmounting data-related challenges in the IoT ecosystem. The prototype serves as a valuable testing ground, providing insights for future improvements. Embracing this state-of-the-art platform, businesses and industries can unlock IoT's full potential, ushering in a new era of efficiency and innovation.
Keywords: IoT ecosystem; IoT platform; Internet of Things; edge computing; Flask; fog computing; cloud computing